PROFIL PERILAKU SOSIAL DENGAN TEMAN SEBAYA DITINJAU DARI ETNIS DAN JENIS KELAMIN PADA SISWA SMA NEGERI 5 PEKANBARU - Nursiah Ulfatari; Elni Yakub; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The social behavior paradigm focuses more on individual relationships with social and non-social environments. Social behavior can grow in the child through interactions that are intertwined with the social environment. A student who is able to socialize well to his environment will be able to place himself in behaving within a social group. Because there are still students who have not been able to put and show social behavior well then in this study felt the need to see the picture of social behavior of students. The purpose of this study is to find out the description of social behavior with peers in terms of ethnicity and gender in role behavior, social relations and expressive behavior. This research uses descriptive quantitative method. Data collection techniques used questionnaires. To analyze data using percentage technique. The sample in this study amounted to 396 students. The results showed the role of ethnic behavior of Java is better than the ethnic Malay, Minang and Batak. While social relations and expressive behavior of ethnic Batak better than ethnic Java, Malay and Minang. As for gender, female role behavior is better than men, in male social relations is better than women, and in expressive behavior of women is better than men.Keywords : Social Behavior, Peers, Ethnicity, Gender